CONFLICT STAGES BETWEEN PT KERETA API AND BANDUNG CITIZEN - Riany Ambonnari Johani; Soni Akhmad Nulhaqim; Arie Surya Gutama (Universitas Padjadjaran, 2018)
ABSTRACTThe research background between PT KAI and citizen is due to densely populated area which is one of the citizen phenomena. The purpose of this research is to describe conflict stages that were occurred. This research used theory regarding conflict stages by Simon fisher which will be implicated toward social work and social worker’s role on conflict resolution. This qualitative descriptive research used study case technique in which informants are chosen based on purposive sampling such as public figure on society, governmental institution, and other party outside citizen and PT KAI. The research result reveal that pre-conflict firstly triggered by claiming of land by PT KAI toward area of resident on west station citizen. The confrontation started when PT KAI spread letter for land clearing toward West station residents. The situation became intense when PT KAI accompanied by police and soldiers came to residents for clearing of houses. It results into 53 families on west station street loss their home as places to shelter and food stall for living. After conflict, there were involvements of Bandung government, student sympathizers, and society organization for conflict resolution that support this problem to be carried out on legal path. The trial was won by residents of west station. This research suggest that there must be recovery program for residents that loss their home and involvement of parties that had crucial roles on society. ABSTRACTThe research background between PT KAI and citizen is due to densely populated area which is one of the citizen phenomena. The purpose of this research is to describe conflict stages that were occurred. This research used theory regarding conflict stages by Simon fisher which will be implicated toward social work and social worker’s role on conflict resolution. This qualitative descriptive research used study case technique in which informants are chosen based on purposive sampling such as public figure on society, governmental institution, and other party outside citizen and PT KAI. The research result reveal that pre-conflict firstly triggered by claiming of land by PT KAI toward area of resident on west station citizen. The confrontation started when PT KAI spread letter for land clearing toward West station residents. The situation became intense when PT KAI accompanied by police and soldiers came to residents for clearing of houses. It results into 53 families on west station street loss their home as places to shelter and food stall for living. After conflict, there were involvements of Bandung government, student sympathizers, and society organization for conflict resolution that support this problem to be carried out on legal path. The trial was won by residents of west station. This research suggest that there must be recovery program for residents that loss their home and involvement of parties that had crucial roles on society.